PHYSICAL EDUCATION AND CONTENTS: RESEARCH ON RELATIOSHIP BETWEEN PHYSICAL EDUCATION AND SPORT DISCIPLINES (Fiep Bulletin - online, 2013)
The Physical Education is compulsory in primary and secondary Italian school (3-19 years olds). The Phusical education programme is 2 hours per week and 60/65 hours per years. The national programme is articulate in four topics: sport, movements and expression, motor skills, health and fitness education. Methods: The data was collect by structured observation in Physical Education Classes. Sample data: 200 schools, 600 classrooms, 15,000 students in Piedmont (nord-west Region of Italy) The sport practice in Federation data was collected by National Institute of Statistic (ISTAT) for CONI (Committee Olympic National Italian); in the years 2004 and 2006. The activities observed are: individual sport (Gymnastics, Athletics, Swimming) and team sport (Volleyball, Basketball, Soccer). Results and discussion: a.The comparison data of secondary between school 1st degree and 2nd degree show a more variety of physical activities in the first (45 kinds of activities and 209 chooses) than the second (42 kinds of activities and 152 chooses). b.The comparison data of secondary school 1st degree and 2nd degree show that the six sport (gymnastics, athletics, swimming, volleyball, basketball, soccer) are about half of all the Physical Education activities (45% in the 1st degree); (60% in the 2nd degree). In the 1st degree the more important PE sport activities are: Basketball (12%); Volleyball (11%); Athletics (10%); Gymnastics (9%); Swimming (3%); Soccer (1%). In the 2nd degree the most important PE sport activities are: Volleyball (16%); Athletics (15%); Basketball (14%); Gymnastics (11%); Swimming (3%); Soccer (3%) Conclusion:. The research show that the Sport Education contents are more practiced in the Physical Education Italian programme. The comparison (between Physical Education contents and federation sport practices) shows the data have the same trend in Physical Education and in Sport Federation practice Soccer shows different trend: the impact in the Physical Education practice is lower (1-3%) than in the sport national federation (30%) for socio-cultural and economics factors.